STRATEGI KOMUNIKASI PEMASARAN PT. PONDOK SOLO PERMAI DALAM MENINGKATKAN MINAT BELI KONSUMEN - Daniswara, Rio (Transformasi, 2015)
The research is qualitative research using data collection technique direct observation to thecourt and interviewing deeply .This report aims to review the communications strategy ofmarketing used by PT. Pondok Solo Permai raising interest in buying consumers. TheInformants in this research is from parties of the company, The General Manager andPersonnel, Head of Marketing and Promotion .Whereas the information from the outside, arefrom some prospective consumers. The results of this study concluded, PT. Pondok SoloPermai succeed in the marketing communications that usingby advertising , brochures ,banners , newspaper , and followed the exhibition that very determined from the quality ofmessage content, communication channel, and hotchpotch promotion used to get the interestof buying consumers .Ke y Words: communications strategy marketing and interest in buying consumers